The highest calling conversations on the American Presidency - Rubenstein, David M. (Simon & Schuster, 2024)
"Blending history and anecdote, Rubenstein chronicles the journeys of the presidents who have defined America as it exists now, what they envision for its future, and their legacy on the world stage. Drawing from his own experience in the Carter administration, he engages in dialogues with our nation's presidents and the historians who study them. Get exclusive access to fresh perspectives, including: original interviews with most of the living US presidents; interviews with noted presidential historians like Annette Gordon-Reed, Ron Chernow, Candice Millard, and more. Through insightful analysis, Rubenstein captures our country's most prominent leaders, the political genius and frays of the presidential role, and the wisdom that emerges from it."
Includes index
Keywords: USA -- Präsident; Geschichte; Politik; Presidents / United States / History; Executive power / United States; United States / Politics and government / History; Présidents / États-Unis / Histoire; Pouvoir exécutif / États-Unis; États-Unis / Politique et gouvernement / Histoire; Interviews; Anecdotes; Interview